Exploring drug resistance genes in Acinetobacter baumannii using metagenomic next-generation sequencing - Li, Guiqiu; Lao, Jianxing; Jiang, Yixiong; Tang, Pei; Huang, Hui; He, Lijuan; Yuan, Ke; Lai, Xiulan (Frontiers in Microbiology, 2025)
IntroductionWith the rising incidence of infectious diseases, the overuse of antibiotics has become a serious problem in clinical practice. In recent years, metagenomic next-generation sequencing (mNGS) has emerged as a promising alternative, offering advantages such as rapid turnaround, broad-spectrum detection, and comprehensive coverage. However, its clinical utility for antimicrobial resistance testing remains to be fully establishedMethodsIn this study, we evaluated the effectiveness of mNGS in detecting antimicrobial resistance in Acinetobacter baumannii using 53 clinical samples. The performance of mNGS was compared with conventional culture-based methods. In addition, clinical judgment of drug resistance was used as a reference to assess concordance between sequencing results and patient treatment.ResultsMetagenomic sequencing produced an average of 8.4 × 10⁷ reads per sample and identified 61 resistance loci—20 of which appeared in at least five isolates. Among the A. baumannii–positive samples, class-specific accuracy of mNGS exceeded 80% for β-lactams, aminoglycosides, quinolones, and minocycline, underscoring its strong performance in comprehensive resistome profiling. We further investigated resistance-associated genes in A. baumannii that appeared with high frequency, including enzymatic inactivation mechanisms (ADC-type cephalosporinases and OXA-type oxacillinases), efflux systems (AbaQ, AbeM), and RND-type efflux pumps (adeIJK/adeN and adeFGH/adeL).DiscussionOur findings demonstrate a high concordance between mNGS results, culture-based methods, and clinical evaluations, highlighting the potential of mNGS as a reliable tool for assessing antimicrobial resistance in A. baumannii.